H2(?=0,1) + C+(2P) ? H+CH+ STATE-TO-STATE RATE CONSTANTS FOR CHEMICAL PUMPING MODELS IN ASTROPHYSICAL MEDIA - Zanchet, Alexandre; Godard, B.; Bulut, Niyazi; Roncero, Octavio; Halvick, Philippe; Cernicharo, Jose (Iop Publishing Ltd, 2013)
State-to-state rate constants for the title reaction are calculated using the electronic ground state potential energy surface and an accurate quantum wave-packet method. The calculations are performed for H-2 in different rovibrational states, nu = 0, 1 and J = 0 and 1. The simulated reaction cross section for nu = 0 shows a rather good agreement with the experimental results of Gerlich et al., both with a threshold of 0.36 eV and within the experimental error of 20%. The total reaction rate coefficients simulated for nu = 1 are two times smaller than those estimated by Hierl et al. from cross sections measured at different temperatures and neglecting the contribution from nu > 1 with an uncertainty factor of two. Thus, part of the disagreement is attributed to the contributions of nu > 1. The computed state-to-state rate coefficients are used in our radiative transfer model code applied to the conditions of the Orion Bar photodissociation region, and leads to an increase of the line fluxes of high-J lines of CH+. This result partially explains the discrepancies previously found with measurements and demonstrates that CH+ excitation is mostly driven by chemical pumping.
Keywords: astrochemistry; molecular data; radiative transfer; scattering